Microbial community analysis and enzymatic process optimization of dry corn stover pretreated with medium-temperature Daqu - YANG Xu, CHU Huiling, SHI Zhiyuan, YUAN Ruihua, TANG Nana, ZHANG Zhiping, SONG Lili, WEI Tao (Zhongguo niangzao, 2025)
In this study, taking dry corn stover (DCS) as a raw material, medium-temperature Daqu were added to DCS samples, the DCS was pretreated by anaerobic fermentation, the organic acids, pH and cellulose fractions during the pretreatment process (0-35 d) were determined, the microbial community structure was analyzed by high-throughput sequencing technology, the principal coordinate analysis (PCoA) was carried out based on the results, and the enzymatic process conditions of DCS after pretreatment were optimized by single factor tests and response surface tests. The results showed that the contents of lactic acid and acetic acid during the pretreatment process of DCS showed an overall increasing trend, and the pH, contents of cellulose and hemicellulose showed a decreasing trend. When adding medium-temperature Daqu fermentation DCS for 28 d, the lactic acid and acetic acid contents, pH, cellulose and hemicellulose contents were 4.07%, 1.06%, 4.83, 30.31% and 17.02%, respectively. In addition, its dominant flora was relatively abundant, the dominant fungal genus was Alternaria (relative abundance 38.85%), and the dominant bacterial genera were Loigolactobacillus, Lactococcus and Enterococcus (relative abundance>1%). PCoA results showed that the microbial community structure remained relatively stable during the DCS pretreatment process of medium-temperature Daqu. The optimal enzymatic process conditions for DCS pretreatment of medium-temperature Daqu for 28 d were as follows: enzymatic hydrolysis time 60 h, substrate mass fraction 9%, and cellulase addition 23 FPU/g cellulose. Under the optimal conditions, the enzymatic hydrolysis rate of cellulose reached 91.87%.